Eudorus and the Early Platonist Interpretation of the Categories - Tarrant, Harold (Laval théologique et philosophique, 2008)
AbstractThe hermeneutic tradition concerning Aristotle’s Categories goes back to Eudorus and his contemporaries in the first century bc. Initially a perplexing text, it forces the Platonist to consider a variety of new dialectical questions. The criticisms of Eudorus demonstrate the desire for orderly arrangements, and pose questions that the hermeneutic tradition, culminating in the magnificent commentary of Simplicius, would try to answer. His pursuit of a critical agenda does not warrant the label “anti-Aristotelian” or “polemical”, but it does show why he preferred to be known as an Academic than as a Peripatetic.